PMO-227 Infliximab induction therapy alone for ulcerative colitis does not result in long term remission. (28th May 2012) - Brooks, A J; Robinson, K; Wright, A; McAlindon, M E; Lobo, A
Abstract : Introduction: Infliximab (IFX) has demonstrated efficacy in moderate to severe ulcerative colitis (UC) with a reduction in short-term colectomy rates. 1 In the UK, the National Institute for Health and Clinical Excellence (NICE) guidance relates to an induction course of three-doses for severely active ulcerative colitis. 2 The aim of this study was to determine outcomes following IFX induction, including colectomy rate, use of corticosteroids (CS) or repeat IFX induction. Methods: Patients with UC at a single large teaching centre received IFX induction for UC requiring hospitalisation or when urgent consideration of surgery was given for resistant or rapidly relapsing disease were retrospectively reviewed (2008–2011). All patients had a Simple Colitis Activity Index (SCAI) at 0, 2, 6 weeks. Results: Twenty-seven patients were studied, median age 38 (range 23–64), with 17 (63%) refractory to oral or intravenous CS (13 and 4 respectively). All received CS in the year preceding IFX; median 1course (range 1–4). 23 (85%) were on immunosuppression (IS) (16 thiopurines, 7 methotrexate), 3 intolerant or non-responsive and 1 naïve to IS. Twenty (74%) received induction IFX alone. Median SCAI was 8 (range 4–13), 4 (range 0–9), 2 (range 0–10) at 0, 2 and 7 weeks respectively. Nine (45%) had a good clinical response, 6 (30%) had a partial response, and 5 (25%) had no response; median SCAI at end of induction 0, 4 and 7 respectively. Colectomy rate at 1 year post IFX induction by response was 2/9 (22%) with a good response, 3/6 (50%) with a partial response, 5/5 (100%) for no response, with partial or no response significantly more likely to result in colectomy compared a good response (p=0.02). Overall, the colectomy rate for induction IFX at 1 year was 0.50 (10/20; 0.30 in 1st 3 months, 0.20 in months 4–12). Seven (35%) required CS at a median of 3 months (range 0–5) and 25% (5/20) a 2 nd induction course of IFX at a median of 4.5 months (range 2–25) post IFX induction. Of these 5, 2 (33%) had a colectomy, 1 is receiving maintenance IFX, 1 had 3 rd induction with IFX, 1 had an infusion reaction and commenced adalimumab. Following initial IFX induction, a further 26% (7/27) received maintenance IFX infusions, median 3 (range 1–6). Of these, 1 receives maintenance IFX, 3 stopped due to lack of funding and are in remission, and 3 (43%) lost response-requiring colectomy. Conclusion: Response to induction IFX determined by SCAI is useful in predicting colectomy in challenging UC patients with resistant or rapidly relapsing UC despite IS. Further induction or maintenance IFX is unlikely to result in remission with partial response on SCAI post induction IFX alone and in this group may be considered as a bridge to surgery. Competing interests: None declared. References: 1. Rutgeerts P, et al. N Engl J Med 2005;353 :2462–76. 2. NICE Guidance 163, 2008.